Nutritional Status of Cancer Patients: A Unicenteric Report from Iran - Farnaz Roshanmehr; Masaharu Kagawa; Farzad Taghizadeh-Hesary; Ali Milani-Bonab; Arezoo Haghighian-Roudsari (Journal of Nutrition and Food Security, 2022)
Considering the incidence of malnutrition, a multidisciplinary approach with targeted nutrition is vital to improve the quality of care in cancer patients. This study aimed to investigate the overall nutritional status of Iranian cancer patients. Methods: This cross-sectional study in 70 cancer patients was conducted in Shohada-e Tajrish Hospital from February to April 2019. The cancer patients were assessed by demographics and Scored Patient-Generated Subjective Global Assessment (PG-SGA) utilized as a common tool to evaluate the nutritional status of patients with different types of cancer. Results: Overall, 20.0% and 70.0% of the patients had normal body mass index (BMI) and overweight/obese, respectively.  Moreover, 30.0% and 60.0% of the participants reported poor and normal intake, respectively. Males were more affected by malnutrition. Approximately 8.0% of the participants lost more than 10.0% of their weight; however, a vast majority of the patients maintained their weight. Conclusion: The high prevalence of malnutrition among the studied cancer patients demonstrated the necessity of nutritional care to improve possible malnutrition for better treatment results.